Enhancement of Nanozyme Permeation by Endovascular Interventional Treatment to Prevent Vascular Restenosis via Macrophage Polarization Modulation. (22nd September 2020) - Feng, Lishuai; Dou, Chaoran; Xia, Yuguo; Li, Benhao; Zhao, Mengyao; El‐Toni, Ahmed Mohamed; Atta, Nada Farouk; Zheng, Yuanyi; Cai, Xiaojun; Wang, Yan; Cheng, Yingsheng; Zhang, Fan
Abstract: The long‐term prognosis of vascular restenosis after endovascular interventional treatment is a critical challenge in a clinical setting. Over‐production of reactive oxygen species (ROS) is a major factor to aggravate vascular restenosis. Current clinical pharmacological interventions for vascular restenosis are still unsatisfactory. Based on the intrinsic ROS scavenging properties, nanozymes have been widely applied in the treatment of inflammatory‐related diseases. However, the vascular endothelial cell barrier hinder the delivery efficiency of intravenously injected nanomaterials in most diseases. Herein, an effective therapeutic strategy for vascular restenosis is developed based on endothelial cells exfoliation by endovascular interventional treatment through vascular balloon injury, which provides an opportunity to enhance nanozyme passive permeation into the vascular intima and uptake by macrophages to alleviate long‐term vascular restenosis in vivo. Moreover, the macrophages polarization modulation mechanism of vascular restenosis prevention is further investigated. This interesting discovery that endothelial cells exfoliation enhanced nanoparticle vascular permeation by endovascular interventional treatment may provide applicative perspectives in the treatment of other disease by nanomaterials. Abstract : Endothelial cells exfoliation induced by endovascular interventional treatment provides an excellent opportunity for nanozymes to passively permeate into vascular intima and accumulate to alleviate long‐term restenosis by reactive oxygen species scavenging in macrophages, macrophages polarization to M2, reduction of the pro‐inflammatory cytokines, accelerated restoration of endothelial cells, and reduced migration and proliferation of smooth muscle cells.